2011
DOI: 10.1088/0957-4484/22/21/215101
|View full text |Cite
|
Sign up to set email alerts
|

Green tea extract selectively targets nanomechanics of live metastatic cancer cells

Abstract: Green tea extract (GTE) is known to be a potential anticancer agent(1) with various biological activities(2, 3) yet the precise mechanism of action is still unclear. The biomechanical response of GTE treated cells taken directly from patient’s body samples was measured using atomic force microscopy(AFM)(4). We found significant increase in stiffness of GTE treated metastatic tumor cells, with a resulting value similar to untreated normal mesothelial cells, whereas mesothelial cell stiffness after GTE treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
44
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(49 citation statements)
references
References 36 publications
5
44
0
Order By: Relevance
“…As for the potential mechanism of changing cell stiffness, we demonstrated an alteration of membrane organization, although cell stiffness is often discussed in relation to the reorganization of cytoskeletal F-actin (Costa 2003;Cross et al 2011). The increase in cell stiffness after treatment with EGCG is related to the sealing effects of EGCG, which inhibit the interaction of ligands with their receptors by alteration of cell membrane organization (Yoshizawa et al 1992;Fujiki 2005;Adachi et al 2007).…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…As for the potential mechanism of changing cell stiffness, we demonstrated an alteration of membrane organization, although cell stiffness is often discussed in relation to the reorganization of cytoskeletal F-actin (Costa 2003;Cross et al 2011). The increase in cell stiffness after treatment with EGCG is related to the sealing effects of EGCG, which inhibit the interaction of ligands with their receptors by alteration of cell membrane organization (Yoshizawa et al 1992;Fujiki 2005;Adachi et al 2007).…”
Section: Discussionmentioning
confidence: 85%
“…Treatment with green tea extract made tumor cells obtained from cancer patients more stiff (Cross et al 2011), and similar investigations revealed that transfection of a metastasis suppressor gene (breast cancer metastasis suppressor 1, BRMS1) increased Young's modulus of metastatic human breast cancer cell line (MDA-MB-435) 3.8 fold and suppressed metastasis (Wu et al 2010). These results suggest that cell stiffness can be altered by treatment with inhibitors of metastasis, such as EGCG, and that an increase in nanomechanical stiffness along with high Young's modulus, that is, rigid elasticity, is associated with inhibition of cell migration.…”
Section: Discussionmentioning
confidence: 88%
“…[8][9][10] Monitoring the mechanical stiffness of living cells can therefore provide a novel way to monitor cell physiology; to detect and diagnose diseases 8 ; and to evaluate the effectiveness of drug treatments. 11,12 Multiple methods including particle-tracking microrheology, [13][14][15][16] magnetic twisting cytometry, 17 micropipette aspiration 18,19 and microindentation [20][21][22] have been developed to measure the elasticity of cells. Particle tracking microrheology traces the thermal vibrations of either submicron fluorescent particles injected into cells or fiducial markers inside the cell cytoskeleton.…”
Section: Introductionmentioning
confidence: 99%
“…[17][18][19][20] Furthermore, changes in cellular nanostructure and nanomechanical properties are useful markers to evaluate curative effects and drug action mechanisms. [21][22][23][24][25] In this investigation, high-resolution AFM imaging and nanoindentation-based soft colloidal force spectroscopy were used to detect real-time changes in melanoma cell morphology, nanostructure, and nanomechanical properties after DTIC treatment, in the context of CD44 modulation.…”
Section: Introductionmentioning
confidence: 99%